2015
DOI: 10.1364/boe.6.000433
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic imaging of acupuncture effect in small animals

Abstract: Acupuncture has been a powerful clinical tool for treating chronic diseases. However, there is currently no appropriate method to clarify the therapeutic effect of acupuncture. Here, we use photoacoustic tomography (PAT) to study the effect of acupuncture on mouse brain blood vessels. Ten healthy mice were stimulated with acupuncture needles on two acupoints. PAT images were obtained before and after acupuncture. We report that stimulation of certain acupoints resulted in changes in hemodynamics/blood flow at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Because the HbT in tissue has a very high light absorption coefficient at 532nm compared with other absorbers, we assumed that the distribution of the RLA represents the distribution of HbT concentration. However, we have demonstrated that this experimental setup can be better applied to acupuncture study in our previous work [26].…”
Section: Methodsmentioning
confidence: 94%
“…Because the HbT in tissue has a very high light absorption coefficient at 532nm compared with other absorbers, we assumed that the distribution of the RLA represents the distribution of HbT concentration. However, we have demonstrated that this experimental setup can be better applied to acupuncture study in our previous work [26].…”
Section: Methodsmentioning
confidence: 94%
“…The KI1 acupoint is located in the middle of the hind paw. The pubic symphysis was obliquely stabbed at point CV4 at the mouse abdomen median line, 10 mm below the navel [22,42,43] (Figure 6B). AG mice received acupuncture at both sides of ST36 and CV4 with 13-mm needles.…”
Section: Acupuncture Manipulationmentioning
confidence: 99%
“…Many studies have shown that there is a relationship between acupoints and functional brain areas. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The ST36 point is located laterally and inferiorly to the knee joint, 3.5 mm below the ca-pitula¯bula. There are many acupoints including the ST36 point in the circulation of Foot-Yangming stomach meridian.…”
Section: Acupoint Selectionmentioning
confidence: 99%
“…[27][28][29][30] An extensive body of research has demonstrated that the regulation e®ect of acupuncture and moxibustion at the acupoints on humans and animals is closely related to the e®ect and adjusting function of the stimulation on the nervous system. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Acupuncture at the peripheral nervous system can exert a di®erent in°uence on the central nervous system including the brain stem, hypothalamus, basal ganglia and cerebral cortex. 39 Previous research in our laboratory has shown that in acupuncture, the Yongquan (KI1) and the Yanglingquan (GB34) acupoints can noninvasively increase the hemodynamics, including the cerebral blood volume (CBV) and total hemoglobin (HbT) in the in vivo mouse brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation